2020
DOI: 10.3390/ijms21062196
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Attenuates Loss of Endothelial Biomarker Expression in Cardio-Endothelial Cells

Abstract: Vitamin D is associated with cardiovascular health through activating the vitamin D receptor that targets genes related to cardiovascular disease (CVD). The human cardiac microvascular endothelial cells (HCMECs) were used to develop mechanically and TGF-β1-induced fibrosis models, and the rat was used as the isoproterenol (ISO)-induced fibrosis model. The rats were injected with ISO for the first five days, followed by vitamin D injection for the consecutive three weeks before being sacrificed on the fourth we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…13 It is shown in clinical and experimental studies that vitamin D could decrease oxidative stress and inflammation. 1416 Vitamin D and its receptor plays a crucial role in the modulation of inflammatory processes and immune function. Many studies both in vivo and in vitro demostrated that Vitamin D inhibits kidney tissue inflammation by reduced generation of proinflammatory cytokines such as interleukin 6 (IL-6), IL-8, IL-12, Tumor Necrosis Factor-α(TNF-α), interferon γ (IFN-γ).…”
Section: Introductionmentioning
confidence: 99%
“…13 It is shown in clinical and experimental studies that vitamin D could decrease oxidative stress and inflammation. 1416 Vitamin D and its receptor plays a crucial role in the modulation of inflammatory processes and immune function. Many studies both in vivo and in vitro demostrated that Vitamin D inhibits kidney tissue inflammation by reduced generation of proinflammatory cytokines such as interleukin 6 (IL-6), IL-8, IL-12, Tumor Necrosis Factor-α(TNF-α), interferon γ (IFN-γ).…”
Section: Introductionmentioning
confidence: 99%
“…Lai et al showed that vit D can increase the protein expression of CD31, and reduce the protein expressions of alpha-smooth muscle actin (α-SMA) and fibronectin in the TGF-β1-induced fibrosis model. Additionally, the protein expression of VE-cadherin was increased and fibroblast-specific protein-1 (FSP1) was decreased after vit D treatment in the isoproterenol-induced fibrosis rat [ 55 ]. Vila et al reported that active vit D rescued the uraemic medium-induced loss of cell-cell adhesion by increasing VE-cadherin and F-actin [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Roffe-Vazquez [9] discuss the molecular mechanisms involved in inflammatory processes, remodeling, fibrosis and atherosclerosis in humans due to a deficiency in vitamin D, through in vitro and animal experimentation. Furthermore, by employing human cardiac microvascular endothelial cells and a rat model of isoproterenol-induced fibrosis, Lai et al [10] specifically report that vitamin D may, in fact, reduce the development of fibrosis. Although more research is required, vitamin D could be part of a prevention strategy for individuals at risk of HF.…”
mentioning
confidence: 99%